Postpartum women's experience of abuse in childhood, postnatal depression, and thoughts of self-harm. (13th November 2019) - Cho, S H; Khang, Y H; June, K J; Lee, J Y; Cho, H J; Kim, Y M
Abstract: Background: Postnatal depression threatens the health of both mothers and babies. To improve maternal and child health in Seoul, South Korea, a nurse home visitation program for pregnant women and new mothers and babies has been implemented since 2013. Methods: Cross-sectional data collected from 9, 124 mothers while they were visiting a public health center for prenatal services or a nurse was visiting their home within 6 weeks after birth between 2014 and 2018 were analyzed. Mothers were asked whether they had experienced physical, emotional, or sexual abuse in their childhood. Postnatal depression and thoughts of self-harm were measured using the Edinburgh Postnatal Depression Scale (EPDS). Postnatal depression was defined as a total EPDS score of 13 or higher; thoughts of self-harm were defined as a response of "yes, quite often, " "sometimes, " or "hardly ever" to the corresponding item, excluding the response of "never". Results: Overall, 3.2% of mothers had experienced child abuse; 8.1% experienced postnatal depression and 5.4% reported thoughts of self-harm. Postnatal depression was more common in mothers who had experienced child abuse than among those who had not (24.2% vs. 7.6%). A similar pattern was found for thoughts of self-harm (21.1% vs. 4.9%, respectively). When controlling for mothers' age, economic status, history of receiving treatment for mental health problems, and other factors, having experienced child abuse was associated with a 2.73-fold increase in the odds of postnatal depression (odds ratio, 2.02-3.70) and a 3.58-fold increase in the odds of thoughts of self-harm (odds ratio, 2.58-4.96). Conclusions: Mothers should be screened for having experienced child abuse when providing public health perinatal care to improve mothers' mental health and parenting practices and to promote their children's growth and development. Key messages: Child abuse may have a lifelong negative effect on victims, and the effect extends to the next generation's health and development. Public health policy and interventions to prevent child abuse are needed to tackle health inequality beginning in early childhood.